Aflatoxin M1 in Dairy Products: Exposure and Health Risks - Berna Madali; Aylin Ayaz (Hacettepe University, 2017)
Aflatoxins are toxic secondary metabolites produced by Aspergillus flavus (Asp.flavus) and Aspergillus parasiticus (Asp. Parasiticus) molds. This mycotoxin group, which is particularly toxic to liver, is found in many cereal crops during growth, harvest, post-harvest and improper storage and in edible tissues of animals consuming contaminating cereal products. Dairy products containing the most aflatoxin residues in edible animal tissues are consumed large quantities by consumers particularly children who are more vulnerable than. Thus, the AFM1 found dairy product is one of the important problems threatening public health. Studies on the AFM1 levels of commercially milk in Turkey is indicated that the AFM1 levels of dairy products do not exceed the acceptable maximum legal limits in the Turkish Food Codex Contaminants Regulation but may pose a risk to health, especially during long term intakes in children. Studies have also shown that AFM1 levels of raw milk contain more AFM1 levels than those sold in the market. Because aflatoxins cannot be completely destroyed from foods and feeds, It is emphasized by the relevant experts that measures should be taken by countries to limit the intake of aflatoxins via diet to minimize potential risks to health and to limit the consumption of aflatoxin containing foods at levels that can not be reduced.